The relationship of maternal age to molar pregnancy incidence, risks for chemotherapy and subsequent pregnancy outcome. (May 2013) - Savage, P. M.; Sita-Lumsden, A.; Dickson, S.; Iyer, R.; Everard, J.; Coleman, R.; Fisher, R. A.; Short, D.; Casalboni, S.; Catalano, K.; Seckl, M. J.
<x xml:space="preserve">Abstract</x> The national registration and treatment service for molar pregnancies in the UK allows for the collection of accurate data on this relatively rare diagnosis. In England and Wales, between 2000 and 2009, 5, 793 patients with complete moles and 7, 790 with partial moles were registered, compared with a total of 8, 242, 511 conceptions. The overall molar pregnancy incidence was 1 for every 607 conceptions (complete mole 1:1, 423; partial mole 1:1, 058), but with major variations with age. For complete moles, the risk varied from < 1:1, 000 for ages 18–40, to 1:156 for women aged 45 and 1:8 for those aged 50 and above. The overall risk of requiring chemotherapy after a complete mole was 13.6% and 1.1% for partial mole, while the risk of a further molar pregnancy in the next conception was 1:68 but each of these figures have considerable variations with age. These modern statistics on molar pregnancy risks and outcomes should be of value to clinicians and their patients, while discussing this rare diagnosis.